Atypical Antipsychotic Lumateperone Effects on the Adrenal Gland With Possible Beneficial Effect of Quercetin Co-administration - El-Haroun, Hala; Ewida, Suzy Fayez; Mohamed, Wael M. Y.; Bashandy, Manar Ali (Frontiers in Physiology, 2021)
Schizophrenia remains one of the most chronic and highly disabling mental disorder. Lumateperone is a recent FDA approved atypical antipsychotic drug for the treatment of schizophrenia. However, the internal FDA pathologist raised many concerns regarding pigment deposition associated with degeneration in different tissue in animal studies with Lumateperone treatment. The adrenal gland may be implicated in lumateperone side effects and Quercetin may have the ability to fulfil this treatment gap. To prove this hypothesis 40 male guinea pigs were used and divided into 4 groups; control, Quercetin-treated, Lumateperone-treated, and Quercetin/ Lumateperone cotreated orally for 28 consecutive days. At the end of treatment, behavioral forced swim (FST) and open field (OF) tests were done. Retro-orbital blood samples were taken for assessment of hormones: ACTH, cortisol, DHEA, and aldosterone, along with assessment of oxidative stress parameters: MDA, GSH, and SOD. Adrenal glands were extracted for histopathological assessment with H&E, Mallory trichome staining, immunostaining, and electron microscopy studies. Lumateperone treated group showed a significant reduction in the activity in FST and OF with histopathological deterioration in adrenal secretory function and structure and increased expression of IL-6, CASPASE-3, collagen deposition, and decreased PCNA. Cytoplasmic vacuolation, pyknosis of the nuclei, increase in the lysosome, lipofuscin pigment, and cellular infiltration with diminishing in the number of secretory granules could all be observed in Lumateperone treated group. Coadministration of Quercetin and lumateperone showed improvement of the previously deteriorated parameters. Quercetin had a prophylactic effect against Lumateperone depressive-like effect on animal behavior and its possible adrenal damage.